Experimental Study on Flow Velocity Structure and Turbulence Characteristics in Open Channel with Biomimetic Grass - Changjing Fu; Jinguo Wang; Tianlong Zhao; Yangming Xu; Yi Lv (Advances in Civil Engineering)
The problem of suspension treatment of oil and gas pipelines has been highly concerned by engineering construction units and researchers. Research shows that the bionic grass can effectively reduce the flow rate, promote sediment deposition, and control the development of the pipeline suspension area. The velocity distribution of open channel flow with bionic grass is very complex. The height and spacing of bionic grass will affect the flow velocity distribution. At present, the flow velocity in open channels containing bionic grass is mainly studied by measuring the velocity variation in the front, middle, and back of bionic grass, but few effective measurements are made for the full velocity field. This paper describes the use of modern means of an advanced test, using standard particle image velocimetry (PIV) measurements with bionic grass along the water channel to the vertical plane of the distribution of the velocity field. The probability density distribution, spatial correlation of pulsating velocity, turbulence intensity, Reynolds stress, and turbulent kinetic energy in the open channel after the protection section of bionic grass were further analyzed.